Singularization, Formation, Ecosophy, Biopotency: to reinvent oneself between the clown and the other - Kátia Maria Kasper (Educação: Teoria e Prática, 2009)
This work presents some aspects of singular and singularized experiences of formation, lived and narrated told by an actor as clown, and establishes connections with other voices, marked by invention of ways of life (DELEUZE, 1965). In the trajectory of construction of the clown “Xuxu”, at the same time, the paper of invention in the construction of subjectivity and the paper of others as an opening to possible worlds are evidenced. (DELEUZE, 1974).